PENGARUH GETARAN DAN KARAKTERISTIK LALU LINTAS TERHADAP BANGUNAN (Studi Kasus Jalan Raya Semarang – Kendal antara Km. 10+000 dan Km. 10+500) - Joko Siswanto; Y.I. Wicaksono (TEKNIK, 2011)
Connections between building damage and vibration intensity has been examined by few researcher. Indeedtackling of effort about bigger damage has been examined too. But connections between traffic character andbig vibration in the street edge isn’t much inspect. Some of literature almost study about connections betweenvibration and traffic micro and too specify, such as to look vibration character and it’s relation with vehiclecharacteristic. Generally details like it is less applicative, Theoretically it’s better do by perform a formula.To aim this study is to examine of connections between vibration in the street edge and traffic characteristic athighway. Traffic characteristic which examined covering are traffic volume and average of traffic speed.To support the aim, survey and analysis is needed. Survey material needs are vibration survey, traffic speed,traffic volume and few road characteristic. Survey did at the street edge with three location where everylocation have few different road characteristic, in this case wide of drainage as of attentuation wide. Everylocations inspected by variable inspection distance are 5 m. 15m and 25 m. Speed and traffic volume datarecorded in every location by using manual record, While vibration data recorded at every point of everylocation by using vibration record Vibecheck meter.Result of recording processed and analyzed to obtain average value and it data distribution. To viewconnections between vibration and traffic characteristic, distance and attentuation, to perform correlation andregretion examine. Regretion examine used for mode calibration connections between vibration and trafficcharacteristic, distance and attentuation based on Watt style.Exams result show that 1) There is strong relation between vibration with distance of examine and attentuationwide, where that connections is negative identifying, 2) There is strong relation between vibration and trafficspeed but not with traffic volume and heave vehicle on the traffic, where that connections is positive identifying,3) Watt style calibration examine result gave good enough result if we look R² value of correlation examineresult which reach 0,96.From analysis result we can concluded some cases, 1) cause vibration is effected by traffic speed then decreaseof vibration effect can performed by limitation speed especially at residence area and 2) cause vibration iseffected by distance and attentuation , then decrease of vibration effect can performed by widest distancebetween building and street edge and widest attentuation in this case is drainage